The Perils of Parliamentarism: Chasing the Flows of the Third Wave of Democratization in Asia - Humagain, Sanjeev; Subedi, Girdhari; Aryal, Tikaram (Journal of APF Command and Staff College, 2020)
What is the present state of democracy among the Asian countries that were (re)democratized during the third wave of democratization? What makes the differences? Why some specific factors play prominent role on the deepening of democracy among them? These are the primary questions of this study. The findings from ten young Asian democracies are as follows. First, all the Asian countries that (re)democratized during the third wave of democratization are practicing democratic system at present. Six of them experienced the breakdowns, while four remain as a continuous democracy. Second, out of eleven structural and institutional factors, examined in this research, only the presidential system has clearer positive impact and economic development has a partial effect on the deepening of democracy. Indirect dictatorship or dominancy of family politics in the parliamentary democracies is found as main reason for the perils of parliamentarism among young Asian democracies.